Proximate Analysis of the Fuel Energy Potential of Guarea Cedrata and Terminalia Catappa - Quartey, Gladys A.; Eshun, John Frank; Marfo, Eric Donkor (European Journal of Applied Sciences, 2022)
Wood has the potential to be used as fuel for electricity production. This is because when the wood is subjected to combustion, it produces biogas in the form of methane, carbon dioxide, and other trace gases. An analysis of the heat value of Guarea cedrata and Terminalia catappa wood species from Ghana was done to ascertain the potential of their biomass to be a solid, natural, and renewable fuel. These species are abundant in this region and can also be grown as plantations. They are also used as furniture and construction materials with a lot of waste which can be made use of in the form of energy. The calorific values of these two tropical species were determined using an oxygen bomb calorimeter. T. catappa had a high calorific value of 18.2539 MJ/kg followed by G. cedrata with a value of 16.6099 MJ/kg. The ash contents of T. catappa were 0.24% and G. cedrata 0.32%. Greater biomass volatile content was shown to lead to greater gas production instead of the solid phase. The volatile matter emitted by the wood species under study was 72.34 % for T. catappa and 68.30 % for G. cedrata. The results showed that the wood of these species can be considered a good potential as a renewable energy resource.